2016
DOI: 10.1159/000444301
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal Nerve Fiber Layer Thickness in Obstructive Sleep Apnea/Hypopnea Syndrome: A Meta-Analysis

Abstract: Purpose: To evaluate and compare changes in retinal nerve fiber layer (RNFL) thickness in patients with obstructive sleep apnea/hypopnea syndrome (OSAHS). Methods: The Cochrane Library, Medline, and Embase were screened using our key words. Results were carefully reviewed to ensure that the included studies met the inclusion/exclusion criteria, and the quality of the studies was assessed using the Newcastle-Ottawa Scale. All included studies categorized patients with OSAHS into 3 groups (mild, moderate, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…The prevalence of NTG was also significantly higher in patients with moderate or severe OSA than in those with no or mild OSA [27]. Several similar studies regarding RNFL thickness and OSA severity were later conducted, and a meta-analysis by Yu et al [37] showed that both moderate and severe OSA were associated with a significant decrease in average, superior, inferior, and nasal RNFL thickness on OCT [37]. Other meta-analysis studies have also provided similar results [38][39][40][41].…”
Section: Discussionmentioning
confidence: 84%
“…The prevalence of NTG was also significantly higher in patients with moderate or severe OSA than in those with no or mild OSA [27]. Several similar studies regarding RNFL thickness and OSA severity were later conducted, and a meta-analysis by Yu et al [37] showed that both moderate and severe OSA were associated with a significant decrease in average, superior, inferior, and nasal RNFL thickness on OCT [37]. Other meta-analysis studies have also provided similar results [38][39][40][41].…”
Section: Discussionmentioning
confidence: 84%
“…Increasing evidence has shown that the longer the duration of oxygen desaturation, the more severe the disease on the optic nerve, thus the thinner the RNFL become [13,22]. Based on this fact, the current study aimed to establish the effects of PAP treatment on RNFL and macula of patients with severe OSAS by using OCT to understand if the effects of OSAS related hypercapnia and hypoxia on these parameters were reversible by PAP treatment or not.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, temporal RNFL is thought to be less susceptible to hypoxemic stress as well as to intracranial hypertension caused by hypoxic and hypercapnic episodes of OSAS. Indeed, in a meta-analysis including 10 studies that analyzes a large sample of OSAS patients with healthy controls, it was found that RNFL in OSAS patients had thinning mostly in the mean, upper, nasal and lower sectors [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal injuries will in turn lead to functional degenerations in contrast sensitivity, dark adaptation, and color vision perception [5]. Moreover, assessments of RNFL thickness have been reported to be indicative of the severity of obstructive sleep apnea/hypopnea syndrome (OSAHSs) [6] and of glaucoma status [7,8].…”
Section: Introductionmentioning
confidence: 99%